KEARIFAN LOKAL SEBAGAI MEDIA PENANAMAN KARAKTER SOSIAL DAN LITERASI SAINS ANAK USIA DINI: KAJIAN LITERATUR SISTEMATIS - Sarina; Indah Kristiani Siringo Ringo; Maronta, Yusuf; Arif Wicaksono, Muhammad; Annisa Akbar, Ayu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Early childhood education (ECE) plays a fundamental role in shaping children's personality and moral foundations, yet the implementation of character education in practice still faces various obstacles due to approaches that tend to be general and less contextual. Meanwhile, the demand for early science literacy is increasingly urgent in the era of globalization, but the ECE curriculum has not yet integrated scientific concepts with culture and environment in an applicable manner. This study aims to synthesize findings regarding the potential of local wisdom as a medium for instilling social character and science literacy in early childhood through a systematic literature review. The method employed is a systematic literature review (SLR) following the PRISMA protocol, which consists of four main stages: identification, screening, eligibility, and inclusion. Literature searches were conducted on reputable academic databases including Scopus, Web of Science, ERIC, and Google Scholar with publication range from 2020 to 2026, using keywords such as "local wisdom," "social character," "science literacy," and "early childhood education." From 227 identified literature sources, 54 articles met the inclusion criteria for further analysis. The results of the analysis using VOSviewer showed that the most dominant keywords were "anak usia dini" (100), "karakter sosial" (95), "early childhood" (90), "local wisdom" (85), and "pendidikan anak usia dini" (80), while "literasi sains" appeared with a frequency of 75 and "kajian literatur sistematis" with a frequency of 65. The main findings reveal that local wisdom has proven effective as a medium for instilling social character through traditional games, folktales, and local rituals, as well as a medium for introducing science literacy through an ethnoscience approach that connects scientific concepts with children's real experiences. This study concludes that local wisdom has significant potential as an integrative medium for instilling social character and science literacy in early childhood, although research on the integration of science literacy remains limited, thus requiring further study development. This study recommends the systematic integration of local wisdom into the ECE curriculum and the development of innovative learning media based on culture and technology.